2011
DOI: 10.1007/s11033-011-1053-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genomic variation in FTO at 16q12.2, MC4R at 18q22 and NRXN3 at 14q31 genes on breast cancer risk

Abstract: Breast cancer is a major cause of cancer-related deaths in women. It is known that obesity is one of the risk factors of breast cancer. The subject of our interest was genes: FTO, MC4R and NRXN3–associated with obesity. In this study we have analyzed frequencies of genomic variants in FTO, MC4R and NRXN3 in the group of 134 breast cancer patients. We genotyped two polymorphic sites located in FTO gene (rs993909 and rs9930506), one polymorphic site of MC4R gene (rs17782313) and one polymorphic site of NRXN3 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 14 publications
1
26
0
1
Order By: Relevance
“…Although it is still not completely clear if the fact of relatively small (3-5 y) age difference between mentioned groups can really affect the results, the further investigation of this subject can have practical significance, considering, e.g., more often occurrence of NRXN3 (neurexin group) gene polymorphism, associated with obesity and cell adhesion, in the youngest group of breast cancer patients. 36 The drawback of the current study is relatively small number of probands in each group, which leads to the conclusion that it should be viewed as a pilot study. Nevertheless, the data obtained is significant and possibly stimulating for further investigation in this area, incorporating the evaluation of not only potential but also actual effects of metformin in comparison with the pattern of studied polymorphisms.…”
Section: Oct1_r61cmentioning
confidence: 94%
“…Although it is still not completely clear if the fact of relatively small (3-5 y) age difference between mentioned groups can really affect the results, the further investigation of this subject can have practical significance, considering, e.g., more often occurrence of NRXN3 (neurexin group) gene polymorphism, associated with obesity and cell adhesion, in the youngest group of breast cancer patients. 36 The drawback of the current study is relatively small number of probands in each group, which leads to the conclusion that it should be viewed as a pilot study. Nevertheless, the data obtained is significant and possibly stimulating for further investigation in this area, incorporating the evaluation of not only potential but also actual effects of metformin in comparison with the pattern of studied polymorphisms.…”
Section: Oct1_r61cmentioning
confidence: 94%
“…A positive association was found only in the case of African American women [38]. Despite the fact that Kaklamani et al [39] reported a significant association between FTO rs1477196 and breast cancer risk in predominantly Caucasian patients, Kusinska et al [40] found no such relation with the FTO variants rs993909 and rs9930506 in a sample of 134 Polish women. The same negative result was obtained by Brooks et al when they tried to find a relationship between FTO variants associated with BMI and the subsequent risk of second primary breast cancer [41].…”
Section: Fto Polymorphisms and Cancermentioning
confidence: 97%
“…Several of these isoforms bind to ligands that include membrane-bound endogenous neuroligins and dystroglycans, soluble endogenous neurexophilins and a-latrotoxin spider neurotoxins [10], [18], [21]. Polymorphic site of NRXN3 gene (rs10146997) was significantly associated with higher risk of breast cancer development [22]. In addition, NRXN3 polymorphisms are associated with alcohol dependence [23].…”
Section: Introductionmentioning
confidence: 99%